Analysis Of Coffee Marketing In Bakadisura Village, Tabang District, Mamasa District, West Sulawesi Province - Yohanis, Yohanis; Surni, Surni; Idrus Salam (International Journal of Technology and Education Research, 2023)
This study aims 1) To find out the pattern of coffee marketing channels in Bakadisura Village, Tabang sub-district, Mamasa district, 2) To find out the margins and marketing profits of coffee beans in Bakadisura Village, Tabang sub-district, Mamasa district . The location of this research was carried out in Bakadisura Village, Tabang District, Mamasa Regency from March to November 2022. The choice of research location was carried out purposively (purposively) with the consideration that Bakadisura Village is a place with the most coffee production. The population or objects in this study were all coffee farmers in Bakadisura Village, Tabang District, Mamasa Regency, totaling 25 families, as well as 2 collectors and 2 wholesalers. Sampling was determined using the census method, so that all coffee farmers and traders in Bakadisura Village became respondents. The results showed that coffee marketing in Bakadisura Village was running efficiently, this was indicated by the FS value = 80% in channel I FS value = 75.55 and 80.35 in channel II. The total profit earned by traders on channel I is Rp. 4,245,775, the profit earned by collector traders on channel II is Rp. 3,531,999, and wholesalers are Rp. 3,085,730.